STUDENTS' TRANSITION FROM TSANAWIYAH TO ALIYAH LEVEL IN ISLAMIC BOARDING SCHOOLS - Marhani, Isnaeni; Mz, Ihsan; Hakim, Azizul (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2025)
Islamic boarding school (Pesantren) is a holistic and integral educational institution, blending religious and general education. The educational process in the internship lasted 24 hours non-stop and was directly supervised by Kiai and Ustadz (pembina). Because of this, the trainees have a very significant role to play in shaping the positive character of the students, through training during the six-year education. This research is aimed at finding factors that influence the decision-making process of continuing education of Tsanawiyah to Aliyah. This research uses qualitative methods with grounded research approach. The research informants were 30 santri (student) from five Pesantren in Makassar City. The findings in this study suggest that the factors that influence Tsanawiyah's continued education to Aliyah are economic factors, personal wants, circle of friend (friendship), family wants and pesantren educational system.